Peningkatan Hasil Belajar Melalui Model Pembelajaran Problem Based Learning di Kelas II SDN Ngaliyan 05 - Ameli, Tesha; Sonia, Fadiya Efi; Khoirunnafiah, Diah; A, Amalia (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Mathematics for grade II aims to The material taught includes basic concepts such as addition, subtraction, multiplication, division, introduction to geometric shapes, measurement, as well as the development of logic and problem solving skills. teaching the basics of mathematics to students, the purpose of this study is to improve the learning outcomes of grade II students in the material of measuring the weight of nonstandard objects at SDN Ngaliya 05 by using a problem-based learning model or Problem Based Learning (PBL). This study used a quantitative approach in the form of an experimental with a one-group pretestposttest design. the population in this study amounted to 13 students with details of 7 male students and 6 female students, the sampling technique used was saturated sample. Data collection techniques with tests, data analysis techniques in the form of normality, homogeneity and hypothesis tests. The results obtained are the pretest obtained an average value of 58.46 with a posttest value of 81.32, based on the results of the t-test sig value (2-tailed) of 0.001